Hipóteses sobre a elevada taxa de juros brasileira: uma abordagem pós-keynesiana - Perfeito, André Guilherme Pereira (2013)
This work aim to organize the main contributions of Brazilian economists (both orthodox and heterodox) about the high interest rates level in Brazil under the current economic crises (2008-2013), and also point out the Keynesian critic about those readings under the Liquid Preference theory of interest. To achieve this goal the work is divided in 3 chapters and also a conclusion where we state our opinion about the high level of interest rate in Brazil and point out problems for further research